Impact of Tax Provisions on Accounting Treatment of Financial Leases with Tax Realization as a Moderating Variable (Case Study at PT. Adira Dinamika Multi Finance Tbk) - Kirana Firda Maharani; Lili Syafitri; Aris Munandar (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to determine the influence provision taxation to treatment accountancy rent use business at PT. Adira Dinamika Multi Finance Tbk . Research data This obtained through distribution questionnaire to sample study that is PT. Adira employees Dinamika Multi Finance Tbk Palembang, which consisted of 95 respondents . Research data analysis techniques use PLS (Partial Least Squares ) technique that is processed with SmartPLS software version 3.2.9. Research results show that Provision Taxation influential positive and significant to Treatment Accountancy Lease at PT. Adira Multifinance Tbk , meanwhile Realization Tax No can moderate influence Provision Taxation to Treatment Accountancy Lease at PT. Adira Multifinance Tbk , which is proven with a negative T -statistic and a value significance on threshold 0.05.